2020
DOI: 10.1302/2046-3758.16.bjo-2020-0067.r1
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with the COVID-19 pandemic in orthopaedics: experiences and procedure in Germany

Abstract: Aims The worldwide COVID-19 pandemic is directly impacting the field of orthopaedic surgery and traumatology with postponed operations, changed status of planned elective surgeries and acute emergencies in patients with unknown infection status. To this point, Germany's COVID-19 infection numbers and death rate have been lower than those of many other nations. Methods This article summarizes the current regimen used in the field of orthopaedics in Germany during the COVID-19 pandemic. Internal university clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…If oxygen saturation fell < 94%, supplemental oxygen therapy was started. Advanced monitoring was started if the patient’s general condition deteriorated, particularly if there was somnolence, delirium, dyspnoea or reduction in oxygen saturation, as recommended by Mueller et al [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If oxygen saturation fell < 94%, supplemental oxygen therapy was started. Advanced monitoring was started if the patient’s general condition deteriorated, particularly if there was somnolence, delirium, dyspnoea or reduction in oxygen saturation, as recommended by Mueller et al [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 positive patients need to be transferred to a black area. In case-positive hospitals which do not possess the potential of spatial separation into these three risk-categories, patients need to be assigned and transferred to a regional tertiary hospital which is able to provide spatial separation [ 32 , 33 ]. Diagnostic-based screening for potentially SARS-CoV-2 positive patients depends on the availability of appropriate testing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that asymptomatic carriers have similar viral loads in their upper respiratory tract to those of symptomatic patients, and can therefore spread COVID-19 with similar virulence, so there is an argument for the regular testing of hospital medical staff working across such sites to confirm their negative status rather than rely just on presence of symptoms (fever, cough, anosmia) in order to maintain safety. 12 Nonetheless, the very low rate of COVID-19 contraction on the elective site with orthopaedic surgery (0.9%) and with soft-tissue surgery (0%) indicated that, practically, this risk may be very low. Thirdly, we acknowledge that only relying only on positive swabs postoperatively to count COVID-19-positive cases postoperatively is a methodological flaw.…”
Section: Discussionmentioning
confidence: 96%
“…COVID-19-free elective patient pathways and precautions continue to evolve with time. 20 , 22 Mueller et al 23 suggested a 14-day isolation period preoperatively with a COVD-19 test immediately prior to surgery, which has been shown to be associated with a low probability of death from COVID-19 postoperatively when the test was negative (i.e. the false negative rate was low).…”
Section: Discussionmentioning
confidence: 99%